Development of compositions of urea greases on aminoamides of fatty acids - Zheleznyi, Leonid; Pop, Grygorii; Papeikin, Oleksii; Venger, Irina; Bodachivska, Larysa (Eastern-European Journal of Enterprise Technologies, 2017)
In the interaction between stearic acid and diamines of different structure we synthesized amino amides. The composition and chemical structure were defined by the spectrometric methods of analysis. We demonstrated the possibility of applying the nitrogen-containing surface-active substances of plant origin as components of dispersed phase of urea thixotropic plastic systems. It was found that urea – a product of the interaction between amino amides of stearic acid and isocyanate – is an effective thickener of petroleum oils. The obtained urea greases are characterized by high levels of thermal, mechanical and colloidal stability. A prospect to saturate the market of lubricants with urea greases produced in Ukraine, using the components obtained from available bio raw materials, predetermined the research into creating balanced lubricating compositions of optimal formulation with correctly chosen basic oils, additives, and fillers. We developed a polyfunctional packet of oleo-additives consisting of sulphur-containing ethyl ester of higher fatty acids of rapeseed oil and the product of condensation of phosphatide concentrate with ethanolamine. It was found that the introduction of these products to the composition of grease on diurea improves its tribological characteristics and anti-oxidation properties, increases the level of biodegradation. Considering the given indicators, the new urea grease is better than some known commercially available analogous products.